Perspectiveness of correction of accompanying diseases in patients with autism by course of interior use of naturally low mineralized water - Gushcha, S. G.; Nasibullin, B. A.; Plakida, A. L.; Volyanska, V. S. (Journal of Education, Health and Sport, 2021)
The article reviews the pathogenesis and the course of autism. Authors define autism as a psychosomatic disorder. A distinctive feature of mineral waters, as natural therapeutic factors of weak intensity, is their pronounced biological activity, the absence of side effects and the possibility of long-term use in combination with medication therapy. The paper presents data substantiating the possibility of using mineral water with an increased content of organic substances for the correction of the somatic component of autism (problems of the gastrointestinal tract, carbohydrate metabolism disorders, neurosis).